2015
DOI: 10.1002/14651858.cd004306.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for smokeless tobacco use cessation

Abstract: Varenicline, nicotine lozenges and behavioural interventions may help ST users to quit. Confidence in results for nicotine lozenges is limited. Confidence in the size of effect from behavioural interventions is limited because the components of behavioural interventions that contribute to their impact are not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 102 publications
2
31
0
Order By: Relevance
“…In contrast, Nethan et al, (2018), in their systematic review indicates that behavioral interventions alone showed high efficacy in SLT cessation among adults with quit rate between 9 -51.5 per cent, at six months. Thus, these evidences are sufficient to initiate SLT/AN related behavioral interventions by nurses as a first step [22][23].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, Nethan et al, (2018), in their systematic review indicates that behavioral interventions alone showed high efficacy in SLT cessation among adults with quit rate between 9 -51.5 per cent, at six months. Thus, these evidences are sufficient to initiate SLT/AN related behavioral interventions by nurses as a first step [22][23].…”
Section: Discussionmentioning
confidence: 97%
“…A Cochrane review by Rice et al, (2017) [21], showed moderate quality evidence to support that advice and support from nurses could increase people's success in quitting smoking, whether in hospitals or in community settings. Though, literature does not reveal any studies related to SLT/AN cessation programmes conducted by nurses, another Cochrane review by Ebbert et al, (2015) summarizes that both pharmacological and behavioral interventions may help SLT users to quit. In contrast, Nethan et al, (2018), in their systematic review indicates that behavioral interventions alone showed high efficacy in SLT cessation among adults with quit rate between 9 -51.5 per cent, at six months.…”
Section: Discussionmentioning
confidence: 99%
“…Concern was raised about possible cardiovascular toxicity due to the nicotine-like effects of varenicline and anecdotal reports of adverse cardiovascular events, but several meta-analyses, a large retrospective cohort study, and clinical trials in smokers with cardiovascular disease, as well as the EAGLES trial, showed no increase in cardiovascular risk ( 147 , 148 ). Varenicline has also been found efficacious for cessation of smokeless tobacco use ( 149 ).…”
Section: Treating Nicotine Addiction In Adults With a Focus On Convementioning
confidence: 99%
“…It admonishes that all health professionals should address tobacco cessation activities as a component of their standard of care service, serve as tobaccofree models for the public, assess exposure to passive smoking, and provide information about avoiding all forms of exposure to tobacco [12]. Literature regarding specific tobacco cessation interventions carried out in Africa is not comprehensive enough to conclude what works and what does not [7,13]. Studies have reported that cessation interventions are well established in developed countries with various literature on what services work through selected professionals on various groups of people [13][14][15].…”
Section: Introductionmentioning
confidence: 99%